Ceramic capacitor material and preparation method of ceramic capacitor

By doping lanthanides into the ceramic capacitor material, a perovskite multi-layer ceramic capacitor with the chemical formula (Bi0.7Ba0.3)1-x(Ca0.7La0.2)x(Fe0.7(1-x)Ti0.3(1-x)+x)O3 was prepared, which solved the problem of low energy storage performance of ceramic capacitors and achieved high energy storage efficiency and high energy storage density.

CN119864237AInactive Publication Date: 2025-04-22INNER MONGOLIA UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510094330.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing ceramic capacitors have low energy storage performance and cannot meet the development needs of electronic devices to miniaturize, integrate and multifunctional.

Method used

A perovskite multilayer ceramic capacitor material with the chemical general formula (Bi0.7Ba0.3)1-x(Ca0.7La0.2)x(Fe0.7(1-x)Ti0.3(1-x)+x)O3 was prepared by doping lanthanides.

Benefits of technology

The energy storage efficiency of the material is achieved by up to 90%, the maximum energy storage density reaches 20.5J/cm3, and the preparation process is simple to operate and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864237A_ABST
    Figure CN119864237A_ABST
Patent Text Reader

Abstract

The invention relates to a ceramic capacitor material and a preparation method of a ceramic capacitor, and the method comprises the following steps: carrying out primary ball milling on Bi2O3, Fe2O3, BaCO3, TiO2, CaCO3 and La2O3, uniformly mixing, pre-sintering at 600-750 DEG C for 3-4 hours to obtain basic ceramic powder with the chemical general formula of (Bi0. 7Ba0. 3) 1-x (Ca0. 7La0. 2) x (Fe0. 7Ti0. 3 (1-x) + x) O3, carrying out ball milling and tape casting on the powder, a solvent, a dispersing agent, an adhesive and a plasticizer to obtain a ceramic thick film, and carrying out secondary ball milling on the ceramic thick film to obtain the ceramic capacitor material. And performing inner electrode printing and sintering on the ceramic thick film to form the ceramic capacitor. By doping the lanthanide elements, the ceramic capacitor with excellent energy storage performance can be prepared, the energy storage efficiency of the material reaches 90% or above, and the maximum energy storage density reaches 20.5 J / cm < 3 >. Moreover, the preparation process is simple to operate and low in cost, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic capacitors, and in particular to a ceramic capacitor material and a method for preparing a ceramic capacitor. Background Art

[0002] In today's era of rapid digitalization and intelligence, electronic devices are everywhere, from daily consumer electronics such as smartphones, tablets, and laptops to high-end fields such as automotive electronics, industrial control, aerospace, and medical equipment. The scale of the electronics industry continues to expand and technology iterations are changing with each passing day. As an indispensable basic electronic component in electronic equipment, dielectric capacitors are becoming increasingly important. However, the current energy storage performance of ceramic capacitors is relatively low and cannot meet the development needs of electronic devices towards miniaturization, integration, and multi-functionality. Therefore, the development of new, green, and high-energy storage density ceramic capacitors has become an urgent task that needs to be solved in the electronics field.

[0003] Common dielectric materials currently include linear dielectrics, ferroelectrics, relaxor ferroelectrics, and antiferroelectrics. Among them, relaxor ferroelectric ceramics have both macroscopic electric domains and polar nano-microdomains. Due to their weak dipole interaction force, they can be restored to a state close to the initial state after the external electric field is removed. Therefore, their residual polarization intensity is significantly reduced, and the hysteresis phenomenon is also suppressed. Therefore, its PE curve is relatively slender. It shows significant advantages of high energy storage density and high energy storage efficiency.

[0004] BiFeO3 (BF) stands out from many materials and becomes one of the preferred green and environmentally friendly material systems for preparing dielectric energy storage capacitors. However, the square hysteresis loop and low breakdown electric field of single-phase BF lead to unsatisfactory energy storage performance. Therefore, researchers have adopted various methods to overcome its shortcomings. According to relevant reports, Zheng et al. 1 / 3 Nb 2 / 3 )O3-modified BF-BT bulk ceramics obtained 1.56 J / cm 3 The energy storage density of the system is 8.12 J / cm 3 It can be seen that the energy storage performance values ​​of BF-based ceramic capacitors reported so far have not yet met expectations. Summary of the invention

[0005] To solve the above problems, an object of the embodiments of the present invention is to provide a ceramic capacitor material and a method for preparing a ceramic capacitor.

[0006] A ceramic capacitor material with the general chemical formula:

[0007] (Bi 0.7 Ba 0.3 ) 1-x (Ca 0.7 La 0.2 ) x (Fe 0.7(1-x) Ti 0.3(1-x)+x )O3, and the value range of x is 0.20~0.35.

[0008] Preferably, the structure of the ceramic capacitor material is an ABO3 perovskite structure.

[0009] The present invention also provides a method for preparing a ceramic capacitor, comprising:

[0010] S1. Ball mill Bi2O3, Fe2O3, BaCO3, TiO2, CaCO3 and La2O3 and mix them evenly. Pre-sinter them at 600-750℃ for 3-4 hours to obtain a product with the general chemical formula (Bi 0.7 Ba 0.3 ) 1-x (Ca 0.7 La 0.2 ) x (Fe 0.7(1-x) Ti 0.3(1-x)+x )O3 based ceramic powder;

[0011] S2, ball-milling the basic ceramic powder obtained in step S1 for a second time and drying it, and then grinding the dried product to pass through a 200-mesh sieve;

[0012] S3, ball-milling the powder obtained in step S2 with a solvent, a dispersant, a binder and a plasticizer to obtain a casting slurry;

[0013] S4, vacuum degassing the tape-casting slurry obtained in step S3, and casting the degassing tape-casting slurry on a tape-casting machine at a speed of 3.5 cm / min to 5 cm / min to obtain a ceramic thick film;

[0014] S5, cutting the dried ceramic thick film into 14×14 cm squares and placing them in a screen printer for internal electrode printing, then cross-stacking the coated internal electrode thick films, and stacking uncoated internal electrode thick film covering layers on the upper and lower surfaces thereof to obtain a laminated green body; S6, subjecting the green body obtained in S5 to lamination hot pressing, cold isostatic pressing and cutting to form a single capacitor green body;

[0015] S7, sintering the capacitor green body;

[0016] S8. Grind both ends of the sintered capacitor and then perform end-sintering treatment to form a ceramic capacitor.

[0017] Preferably, in S1, the purity of Bi2O3, Fe2O3, BaCO3, TiO2, CaCO3 and La2O3 is higher than 90%.

[0018] Preferably, the first ball milling time is 18 to 24 hours, the heating rate of the pre-calcination is 2 to 5°C / min, and the cooling rate is 3°C / min; the second ball milling time is 18 to 24 hours.

[0019] Preferably, in S3, the solvent is 15-30wt% anhydrous ethanol of the powder, the dispersant is 0.8-2wt% tributyl phosphate of the powder, the binder is 8-20wt% polyvinyl butyral of the powder, the plasticizer is 1.2-2.5wt% dibutyl phthalate of the powder, and the ball milling time is 12-18 hours.

[0020] Preferably, in S5, the inner electrode slurry is Pt slurry, and the number of dielectric layers in the green body after lamination is 6.

[0021] Preferably, in S6, the laminated green body is placed in a tablet press, the temperature is maintained at 45-60°C, the pressure is maintained at 8-15 MPa for hot pressing for 15-30 minutes, the pressure is maintained at 150-200 MPa for 10-30 minutes, cold isostatic pressing is performed, and the laminated green body after cold isostatic pressing is cut to form a single capacitor green body.

[0022] Preferably, in S7, the capacitor green body is placed in a muffle furnace, heated at a heating rate of 0.1°C / min to 0.5°C / min, the holding temperature is 500 to 650°C, and the holding time is 6 hours, the organic matter remaining in the capacitor green body is removed, and the sample after debinding is sintered at a heating rate of 2 to 7°C / min, a temperature of 950 to 1020°C, and a holding time of 2 to 4 hours.

[0023] Preferably, in S8, the two ends of the sintered capacitor are polished and coated with terminal electrode silver paste, and then placed in a tube furnace and kept at a sintering temperature of 750° C. for 15 minutes to perform sintering treatment to obtain a ceramic capacitor.

[0024] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects:

[0025] The present invention relates to a ceramic capacitor material and a preparation method of the ceramic capacitor. Compared with the prior art, the present invention can prepare a perovskite multilayer ceramic capacitor with excellent energy storage performance by doping lanthanide elements. The energy storage efficiency of the material is as high as more than 90%, and the maximum energy storage density reaches 20.5 J / cm 3Moreover, the preparation process is simple to operate, low in cost, can be stably and repeatedly prepared, and has broad application prospects.

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 The XRD spectrum of the bismuth ferrite-based multilayer ceramic capacitor with high energy storage performance prepared by the present invention.

[0029] Figure 2 The hysteresis loop of the bismuth ferrite-based multilayer ceramic capacitor with high energy storage performance prepared by the present invention at 1490 kV / cm;

[0030] Figure 3 The scanning electron microscope cross-sectional image and Pt and O element energy spectra of the bismuth ferrite-based multilayer ceramic capacitor with high energy storage performance prepared by the present invention;

[0031] Figure 4 The temperature dependence of the dielectric constant and dielectric loss at the same frequency of the bismuth ferrite-based multilayer ceramic capacitor with high energy storage performance prepared by the present invention;

[0032] Figure 5 This is a schematic diagram of the structure of a ceramic capacitor provided by the present invention. DETAILED DESCRIPTION

[0033] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0034] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0035] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0036] Embodiment 1:

[0037] A ceramic capacitor material with the general chemical formula:

[0038] (Bi 0.7 Ba 0.3 ) 1-x (Ca 0.7 La 0.2 ) x (Fe 0.7(1-x) Ti 0.3(1-x)+x )O3, and the value range of x is 0.20 to 0.35. The structure of the ceramic capacitor material is ABO3 perovskite structure.

[0039] The present invention provides a method for preparing a ceramic capacitor based on a ceramic capacitor material, comprising:

[0040] S1. Ball mill Bi2O3, Fe2O3, BaCO3, TiO2, CaCO3 and La2O3 for 18 to 24 hours, pre-sintering at a heating rate of 2 to 5°C / min and a cooling rate of 3°C / min, then mix them evenly, pre-sinter at 600 to 750°C for 3 to 4 hours, and obtain the chemical formula:

[0041] (Bi 0.7 Ba 0.3 ) 1-x (Ca 0.7 La 0.2 ) x (Fe 0.7(1-x) Ti 0.3(1-x)+x )O3 based ceramic powder;

[0042] In S1, the purity of Bi2O3, Fe2O3, BaCO3, TiO2, CaCO3 and La2O3 is higher than 90%.

[0043] S2, ball-milling the basic ceramic powder obtained in step S1 for a second time and drying it, and then grinding the dried product to pass through a 200-mesh sieve;

[0044] S3. Ball-milling the powder obtained in step S2 with a solvent, a dispersant, a binder and a plasticizer to obtain a casting slurry; in S3, the solvent is 15-30wt% anhydrous ethanol of the powder, the dispersant is 0.8-2wt% tributyl phosphate of the powder, the binder is 8-20wt% polyvinyl butyral of the powder, the plasticizer is 1.2-2.5wt% dibutyl phthalate of the powder, and the ball milling time is 12-18 hours.

[0045] S4, vacuum degassing the tape-casting slurry obtained in step S3, and casting the degassing tape-casting slurry on a tape-casting machine at a speed of 3.5 cm / min to 5 cm / min to obtain a ceramic thick film;

[0046] S5. Cut the dried ceramic thick film into 14×14 cm squares and place them in a screen printer for internal electrode printing. Then, cross-stack the coated internal electrode thick films, and then stack uncoated internal electrode thick film covering layers on the upper and lower surfaces to obtain a laminated green body. In S5, the internal electrode slurry is Pt slurry, and the number of dielectric layers in the laminated green body is 6.

[0047] S6, the green billet obtained in S5 is subjected to lamination hot pressing, cold isostatic pressing and cutting to form a capacitor green billet; in S6, the laminated green billet is placed in a tablet press, the temperature is maintained at 45-60°C, the pressure is maintained at 8-15 MPa for hot pressing for 15-30 minutes, the pressure is maintained at 150-200 MPa for 10-30 minutes, cold isostatic pressing is performed, and the laminated green billet after cold isostatic pressing is cut to form a single capacitor green billet.

[0048] S7, sintering the capacitor green body;

[0049] In S7, the capacitor green body is placed in a muffle furnace, heated at a heating rate of 0.1°C / min to 0.5°C / min, and the holding temperature is 500 to 650°C for 6 hours to remove the residual organic matter in the capacitor green body. The debinding sample is sintered at a heating rate of 2 to 7°C / min, a temperature of 950 to 1020°C, and a holding time of 2 to 4 hours.

[0050] S8, grinding both ends of the sintered capacitor, and then performing end-sintering treatment to form a ceramic capacitor, such as Figure 5 shown.

[0051] In S8, both ends of the sintered capacitor are polished and coated with terminal electrode silver paste, and then placed in a tube furnace and kept at a sintering temperature of 750° C. for 15 minutes to perform sintering treatment to obtain a ceramic capacitor.

[0052] Embodiment 2:

[0053] This embodiment provides a method for preparing a bismuth ferrite-based multilayer ceramic capacitor with high energy storage performance, which is completed by the following steps:

[0054] (1) According to the chemical formula (Bi 0.7 Ba 0.3 ) 1-x (Ca 0.7 La 0.2 ) x (Fe 0.7(1-x) Ti 0.3(1-x)+x )O3, where x=0.2 in the stoichiometric ratio, weigh 79.3776g of 99% pure Bi2O3, 25.9082g of 99% Fe2O3, 27.4428g of 99% BaCO3, 20.5706g of 98% TiO2, 8.9310g of 90% CaCO3 and 3.7383g of 99.99% La2O3 as raw materials, and use deionized water as the medium for ball milling and mixing for 18 hours. Then place the powder in a muffle furnace, heat it to 600℃ at a heating rate of 3℃ / min, and keep it warm for 4 hours under this condition to obtain the basic ceramic powder, and then perform a second ball milling, drying and grinding.

[0055] (2) The obtained basic ceramic powder solvent is mixed with 15wt% anhydrous ethanol, the dispersant is 0.8wt% tributyl phosphate, the binder is 8wt% polyvinyl butyral, and the plasticizer is 1.2wt% dibutyl phthalate. The ball milling time is 12 hours. The mixed solution is vacuum defoamed, and then the casting slurry is cast on a casting machine at a speed of 3.5cm / min to obtain a ceramic thick film. The dried ceramic thick film is cut into 14×14cm squares, and the ceramic thick film is placed in a screen printer for Pt electrode printing. Then, the coated inner electrode thick film is cross-laminated, and then the uncoated inner electrode thick film covering layer is stacked on the upper and lower surfaces to obtain a green body after lamination. Hot press at a temperature of 45°C and a pressure of 8MPa for 15 minutes. Cold isostatic pressing is maintained at 200MPa for 15 minutes. The cold isostatically pressed MLCC is cut to obtain a single green body.

[0056] (3) The capacitor green body is placed in a muffle furnace, heated at a heating rate of 0.1°C / min, and kept at 500°C for 6 hours to remove the residual organic matter in the ceramic body. The debinding sample is sintered at a heating rate of 2°C / min and at a temperature of 950°C for 3 hours. The sintered sample is polished and then coated with terminal electrode silver paste. It is then placed in a tubular furnace and kept at a sintering temperature of 750°C for 15 minutes to obtain a ceramic capacitor with high energy storage performance.

[0057] Embodiment 3:

[0058] (1) According to the chemical formula (Bi 0.7 Ba 0.3 ) 1-x (Ca 0.7 La 0.2 ) x (Fe 0.7(1-x) Ti 0.3(1-x)+x )O3, where x=0.25 in the stoichiometric ratio, weigh 76.4219g of 99% pure Bi2O3, 24.9435g of 99% Fe2O3, 26.4209g of 99% BaCO3, 22.8054g of 98% TiO2, 11.4646g of 90% CaCO3 and 4.7988g of 99.99% La2O3 as raw materials, and use deionized water as the medium for ball milling and mixing for 20 hours. Then place the powder in a muffle furnace, heat it to 650℃ at a heating rate of 3℃ / min, and keep it warm for 4 hours under this condition to obtain the basic ceramic powder, and then perform a second ball milling, drying and grinding.

[0059] (2) The obtained basic ceramic powder solvent is mixed with 20wt% anhydrous ethanol, the dispersant is 1.0wt% tributyl phosphate, the binder is 10wt% polyvinyl butyral, and the plasticizer is 1.5wt% dibutyl phthalate. The ball milling time is 14 hours. The mixed solution is vacuum defoamed, and then the casting slurry is cast on a casting machine at a speed of 4.0cm / min to obtain a ceramic thick film. The dried ceramic thick film is cut into 14×14cm squares, and the ceramic thick film is placed in a screen printer for Pt electrode printing. Then, the coated inner electrode thick film is cross-laminated, and then the uncoated inner electrode thick film covering layer is stacked on the upper and lower surfaces to obtain a green body after lamination. Hot press at a temperature of 50°C and a pressure of 10MPa for 20 minutes. Cold isostatic pressing is maintained at 200MPa for 15 minutes. The cold isostatically pressed MLCC is cut to obtain a single green body.

[0060] (3) The capacitor green body is placed in a muffle furnace and heated at a heating rate of 0.2°C / min, with a holding temperature of 550°C for 6 hours to remove the residual organic matter in the ceramic body. The debinding sample is sintered at a heating rate of 3°C / min and a temperature of 980°C for 3 hours. The sintered sample is polished and then coated with terminal electrode silver paste. It is then placed in a tubular furnace and sintered at a sintering temperature of 750°C for 15 minutes to obtain a ceramic capacitor with high energy storage performance.

[0061] Embodiment 4:

[0062] (1) According to the chemical formula (Bi 0.7 Ba 0.3 ) 1-x (Ca 0.7 La 0.2 ) x (Fe 0.7(1-x) Ti 0.3(1-x)+x )O3, where x=0.3 in the stoichiometric ratio, weigh 73.3024g of 99% pure Bi2O3, 23.9253g of 99% Fe2O3, 25.3425g of 99% BaCO3, 25.1639g of 98% TiO2, 14.1385g of 90% CaCO3 and 5.9181g of 99.99% La2O3 as raw materials, and use deionized water as the medium for ball milling and mixing for 22 hours. Then the powder is placed in a muffle furnace, heated to 700°C at a heating rate of 3°C / min, and kept warm for 4 hours under this condition to obtain the basic ceramic powder, and then the second ball milling, drying and grinding are carried out.

[0063] (2) The obtained basic ceramic powder solvent is mixed with 25wt% anhydrous ethanol, the dispersant is 1.5wt% tributyl phosphate, the binder is 15wt% polyvinyl butyral, and the plasticizer is 2wt% dibutyl phthalate. The ball milling time is 16 hours, and the mixed solution is vacuum defoamed. Then, the casting slurry is cast on a casting machine at a speed of 4.5cm / min to obtain a ceramic thick film. The dried ceramic thick film is cut into 14×14cm squares, and the ceramic thick film is placed in a screen printer for Pt electrode printing. Then, the coated inner electrode thick film is cross-laminated, and then the uncoated inner electrode thick film covering layer is stacked on the upper and lower surfaces to obtain a green body after lamination. Hot press at a temperature of 55°C and a pressure of 12MPa for 25 minutes. Cold isostatic pressing is maintained at 200MPa for 15 minutes. The cold isostatically pressed MLCC is cut to obtain a single green body.

[0064] (3) The capacitor green body is placed in a muffle furnace, heated at a heating rate of 0.3°C / min, and kept at 600°C for 6 hours to remove the residual organic matter in the ceramic body. The debinding sample is sintered at a heating rate of 5°C / min and a temperature of 1000°C for 3 hours. The sintered sample is polished and then coated with terminal electrode silver paste. It is then placed in a tubular furnace and kept at a sintering temperature of 750°C for 15 minutes to obtain a ceramic capacitor with high energy storage performance.

[0065] Embodiment 5:

[0066] (1) According to the chemical formula (Bi 0.7 Ba 0.3 ) 1-x (Ca 0.7 La 0.2 ) x (Fe 0.7(1-x) Ti 0.3(1-x)+x )O3, where x=0.35 in the stoichiometric ratio, weigh 70.0053g of 99% pure Bi2O3, 22.8492g of 99% Fe2O3, 24.2026g of 99% BaCO3, 27.6567g of 98% TiO2, 16.9648g of 90% CaCO3 and 7.1010g of 99.99% La2O3 as raw materials, and use deionized water as the medium for ball milling and mixing for 24 hours. Then place the powder in a muffle furnace, heat it to 750℃ at a heating rate of 3℃ / min, and keep it warm for 4 hours under this condition to obtain the basic ceramic powder, and then perform a second ball milling, drying and grinding.

[0067] (2) The obtained basic ceramic powder solvent is mixed with 30wt% anhydrous ethanol, the dispersant is 2wt% tributyl phosphate, the binder is 20wt% polyvinyl butyral, and the plasticizer is 2.5wt% dibutyl phthalate. The ball milling time is 18 hours. The mixed solution is vacuum defoamed, and then the casting slurry is cast on a casting machine at a speed of 5cm / min to obtain a ceramic thick film. The dried ceramic thick film is cut into 14×14cm squares, and the ceramic thick film is placed in a screen printer for Pt electrode printing. Then, the coated inner electrode thick film is cross-laminated, and then the uncoated inner electrode thick film covering layer is stacked on the upper and lower surfaces to obtain a green body after lamination. Hot press at a temperature of 60°C and a pressure of 15MPa for 30 minutes. Cold isostatic pressing is maintained at 200MPa for 15 minutes. The cold isostatically pressed MLCC is cut to obtain a single green body.

[0068] (3) The capacitor green body is placed in a muffle furnace and heated at a heating rate of 0.5°C / min, and the heat preservation temperature is 600°C for 6 hours to remove the residual organic matter in the ceramic body. The debinding sample is sintered at a heating rate of 7°C / min and a temperature of 1020°C for 3 hours. The sintered sample is polished and then coated with terminal electrode silver paste. It is then placed in a tubular furnace and sintered at a sintering temperature of 750°C for 15 minutes to obtain a ceramic capacitor with high energy storage performance.

[0069] Figure 1 The XRD spectrum of the bismuth ferrite-based multilayer ceramic capacitor with high energy storage performance prepared in Example 2-5. It can be seen from the figure that the ceramic forms a pure perovskite phase structure, and no impurity phase is detected.

[0070] Figure 2 This is the hysteresis loop of the bismuth ferrite-based multilayer ceramic capacitor with high energy storage performance prepared in Example 4 at 1490 kV / cm. It can be seen from the figure that under high electric field, the residual polarization intensity P of the multilayer ceramic capacitor r Very low, saturation polarization intensity P max Large, reaching 20.5J / cm at 1490kV / cm 3 The releasable energy storage density and energy storage efficiency of 91.3% are achieved.

[0071] Figure 3 The scanning cross-sectional view and Pt electrode element spectrum diagram of the bismuth ferrite-based multilayer ceramic capacitor with high energy storage performance prepared in Example 4. At this time, the average thickness of the single-layer capacitor dielectric layer is 15μm, and the average thickness of the electrode layer is 4μm. By micrometer-scale regulation of the dielectric layer, reducing the thickness of the dielectric layer can improve the breakdown strength, thereby improving the energy storage performance of the capacitor. The element distribution of the cross section of the MLCC was observed by energy spectrum testing. At this time, the Pt electrode is well distributed and the electrode is continuous. This shows that the electrode has not diffused in the capacitor, indicating that the electrode and the dielectric layer can be well matched at this sintering temperature.

[0072] Figure 4 The temperature dependence of εr and tanδ at different frequencies of the bismuth ferrite-based multilayer ceramic capacitor with high energy storage performance prepared in Example 4, two important features can be noticed in the data, the frequency dispersion behavior and the dispersion phase change behavior, which show stable changes.

[0073] Figure 5 Schematic diagram of the structure of the ceramic capacitor of Example 2-5, where the number of dielectric layers is 6.

[0074] According to the specific embodiments of the present invention, the present invention achieves the following beneficial effects:

[0075] (1) The bismuth ferrite base of the present invention has a large P r And the lower resistance is not suitable for use in the field of pulse energy storage alone. The selection system of the present invention is: (Bi 0.7 Ba 0.3 ) 1-x (Ca 0.7 La 0.2 ) x (Fe 0.7(1-x) Ti 0.3(1-x)+x )O3. The reasons are as follows: a. Due to the difference in valence state and ionic radius, the long-range ordered ferroelectric domain structure is destroyed and the relaxation behavior is enhanced; b. Considering La 3+ It can effectively refine the grains, which is beneficial to the improvement of the breakdown electric field, thereby obtaining lead-free multilayer ceramic capacitors with ultra-high energy storage density, high efficiency and high stability.

[0076] (2) The present invention solves the problem of relatively low energy storage performance of BF-based ferroelectric ceramics in the prior art. Based on the regulation of grain size and domain structure, the present invention designs (Bi 0.7 Ba 0.3 ) 1-x (Ca 0.7 La 0.2 ) x (Fe 0.7(1-x) Ti 0.3(1-x)+x ) The average grain size of O3 multilayer ceramic capacitors is at the submicron level, the thickness of a single dielectric layer is 15 to 20 microns, and the energy storage density is W rec >20J / cm 3 , energy storage efficiency> 90%. The comprehensive energy storage performance obtained is significantly better than most lead-free multilayer ceramic capacitors that have been reported so far.

[0077] (3) The raw materials used in the present invention are all green and environmentally friendly, the preparation process is simple to operate, and the cost is low.

[0078] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technical solution that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A ceramic capacitor material, characterized in that: The general chemical formula is (Bi 0.7 Ba 0.3 ) 1-x (Ca 0.7 La 0.2 ) x (Fe 0.7(1-x) Ti 0.3(1-x)+x )O3, and the value range of x is 0.20~0.

35.

2. A ceramic capacitor material according to claim 1, characterized in that: The structure of ceramic capacitor material is ABO3 perovskite structure.

3. A method for preparing a ceramic capacitor, characterized in that: include: S1. Ball mill Bi2O3, Fe2O3, BaCO3, TiO2, CaCO3 and La2O3 and mix them evenly. Pre-sinter them at 600-750℃ for 3-4 hours to obtain a product with the general chemical formula (Bi 0.7 Ba 0.3 ) 1-x (Ca 0.7 La 0.2 ) x (Fe 0.7(1-x) Ti 0.3(1-x)+x )O3 based ceramic powder; S2, ball-milling the basic ceramic powder obtained in step S1 for a second time and drying it, and then grinding the dried product to pass through a 200-mesh sieve; S3, ball-milling the powder obtained in step S2 with a solvent, a dispersant, a binder and a plasticizer to obtain a casting slurry; S4, vacuum degassing the tape-casting slurry obtained in step S3, and casting the degassing tape-casting slurry on a tape-casting machine at a speed of 3.5 cm / min to 5 cm / min to obtain a ceramic thick film; S5, cutting the dried ceramic thick film into a 14×14 cm square and placing it in a screen printer for internal electrode printing, then cross-stacking the coated internal electrode thick films, and then stacking uncoated internal electrode thick film covering layers on the upper and lower surfaces thereof to obtain a laminated green body; S6, forming a single capacitor green body by laminating hot pressing, cold isostatic pressing and cutting the green body obtained in S5; S7, sintering the capacitor green body; S8. Grind both ends of the sintered capacitor and then perform end-sintering treatment to form a ceramic capacitor.

4. The method for preparing a ceramic capacitor according to claim 3, characterized in that: In S1, the purity of Bi2O3, Fe2O3, BaCO3, TiO2, CaCO3 and La2O3 is higher than 90%.

5. The method for preparing a ceramic capacitor according to claim 3, characterized in that: The first ball milling time is 18 to 24 hours, the pre-burning heating rate is 2 to 5°C / min, and the cooling rate is 3°C / min; the second ball milling time is 18 to 24 hours.

6. The method for preparing a ceramic capacitor according to claim 3, characterized in that: In S3, the solvent is 15-30wt% anhydrous ethanol of the powder, the dispersant is 0.8-2wt% tributyl phosphate of the powder, the binder is 8-20wt% polyvinyl butyral of the powder, the plasticizer is 1.2-2.5wt% dibutyl phthalate of the powder, and the ball milling time is 12-18 hours.

7. The method for preparing a ceramic capacitor according to claim 3, characterized in that: In S5, the inner electrode slurry is Pt slurry, and the number of dielectric layers in the green body after lamination is 6.

8. The method for preparing a ceramic capacitor according to claim 3, characterized in that: In S6, the laminated green body is placed in a tablet press, the temperature is maintained at 45-60°C, the pressure is maintained at 8-15 MPa for hot pressing for 15-30 minutes, the pressure is maintained at 150-200 MPa for 10-30 minutes, cold isostatic pressing is performed, and the laminated green body after cold isostatic pressing is cut to form a single capacitor green body.

9. The method for preparing a ceramic capacitor according to claim 3, characterized in that: In S7, the capacitor green body is placed in a muffle furnace, heated at a heating rate of 0.1°C / min to 0.5°C / min, and the holding temperature is 500 to 650°C for 6 hours to remove the residual organic matter in the capacitor green body. The debinding sample is sintered at a heating rate of 2 to 7°C / min, a temperature of 950 to 1020°C, and a holding time of 2 to 4 hours.

10. The method for preparing a ceramic capacitor according to claim 3, characterized in that: In S8, both ends of the sintered capacitor are polished and coated with terminal electrode silver paste, and then placed in a tube furnace and kept at a sintering temperature of 750° C. for 15 minutes to perform sintering treatment to obtain a ceramic capacitor.

Citation Information

Patent Citations

  • Method for preparing bismuth ferrite based multifunctioanl oxide ceramic material

    CN101050120A

  • Capacitor, storage and manufacture methods for capacitor and storage

    CN102544020A

  • Lead-free bismuth ferrite-based ceramic material and preparation method thereof

    CN111205082A